A Comprehensive Review of Jatamansi (Nardostachys Jatamansi) (AYUSHDHARA, 2021)
Jatamansi, that is Nardostachys jatamansi, is a well-known plant used in Ayurveda classics, which is used in “nervous headache, excitement, menopausal symptoms, flatulence, epilepsy and intestinal colic”. A lot of research has also been conducted on this plant exploring its pharmacological utilization. Though there are many review articles available on this plant but no review has comprehensively covered all aspects of Jatamansi. Objectives: This article is thus aim to collect and comprehensively review information available regarding the medicinal use of Jatamansi and identify areas that need further research. Data source: Jatamansi (Nardostachys jatamansi) was reviewed from Samhitas and from more than 55 research articles for medicinal uses and other important aspects. Review methods: This review is in a narrative format and done from literature and publications relevant to Jatamansi that were identified through a systematic search of major computerized medical databases. Result: Jatamansi (Nardostachys jatamansi) is concluded to have indications- Vatavyadhi, Shotha, Shoola, Daha, Varnavikara, Swedadhikya, Apasmara, Apatantraka, Unmada, Manasavikara, Mastishkadaurbalya, Shirahshoola, Agnimandya, Anaha, Udarashoola, Chhardi, Kamala, Hriddrava, Raktabharadhikya, Arsha, Hikka, Kasa, Shwasa, Mootrakrichchhra, Klaibya, Sadyovrana, Bhagna, Garbhashayashotha, Twagvikara, Vatarakta, Sannipatika jwara, Mukharoga, Netraroga, Vishavikara & Bhootabadha. Jatamansi also possesses activities like hepatoprotective, antifungal and antibacterial, cardio protective, hypolipidemic, antidepressant, antioxidant, neuroprotective, antiparkinson, anticonvulsant, antihyperglycemic, nootropic, anticancer and radioprotective. Conclusion: Ayurvedic indications of Nardostachys jatamansi are compared with Article concluded effect and then areas of further research are identified.